ANALISIS RESISTANSI PENTANAHAN SEBAGAI UPAYA UNTUK ANTISIPASI SAMBARAN PETIR DI DAERAH PERBUKITAN WILAYAH BANTUL - Suyanto, Muhammad; Mulyaningsih, Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
The aim of this study was to find an information about varying soil resistant along residence area in Bantul Regency. The aim of the study is to compiling fixed grounding system. Factors controlling the grounding are ground resistivity, electrode resistivity, environmental condition, size and shape of the system. Ground resistivity needs a good grounding system, that accomplish to savety standard for people and its equipments. The ground system should be able to prevent dangerous caused by flash, whenever nuisance come out. It parposes to overcoming the current of ground system nuisance of electricity power, in order the power could be flowing to the ground, directly; not to the equipments. The resistivity data resulted from the field work measurements, shows some different va-lues in each place, that probably caused by different kinds of soils. For examples are re-gusol soil has a resistivity value of 22.05Ω, latosol 17.04Ω, and red mediteran 15.12Ω. Grumusol soil has resistivity of 7.8Ω, but after it’s analyzed by grounding with 4 electrode, the value is decrease into 4.22Ω. Those are caused by grumusol soil is clayy, while the other soils are sandy. Based of IEEE recomendation of ground resistivity values, home electricity should be <10Ω, while for flash protection should be < 5Ω. Up to now, the solu-tion for quenching the overload power, in order it’s unable to damage the equipments, it’s flowed to the ground directly.